Attacking profiles in elite hurling. (4th May 2017) - Clear, Colm; Hughes, Mike; Martin, Denise
Abstract: This study investigated the effectiveness of different attacking profiles for elite hurling to establish if certain patterns can be used to improve performance. Every possession in play ( n  = 4260) in the 2015 Senior Inter-County Hurling competition ( n  = 28 games) was characterised using 6 variables; how possession was gained, start location, pass count, pass pattern, end location and outcome using NacSport Scout Plus. A binomial logistic regression comparing total shot count (  = 21.961, p  < .001), total shot efficiency (  = 4.244, p  = .050), shot count from play (  = 17.647, p  < .001) and shot efficiency from play (  = 8.389, p  = .009) between winning and losing teams, revealed these variables are significantly associated with winning. The additional key finding for coaches is: (1) the need to design one and two pass possession games to meet the current demands of the game, (2) teams that take the most shots win, therefore encourage players to shoot, (3) implying a high defensive press was shown to be an effective attacking strategy and (4) tier 2 teams can significantly improve their chances of winning by having an efficient free taker.